2013
DOI: 10.1007/s00347-013-2918-7
|View full text |Cite
|
Sign up to set email alerts
|

Operation nach Hughes und damit kombinierte Verfahren

Abstract: The Hughes procedure is a well-suited technique for eyelid reconstruction of shallow defects extending beyond 10 mm horizontally and involving up to 100 % of the eyelid. The latter require a combined procedure such as the Hughes procedure and an autologous tarsoconjunctival flap and skin graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
2
3
0
1
Order By: Relevance
“…The high functional-esthetical success rate of the modified Hughes procedure, observed in this study, corresponds with the beneficial results, which have been reported in previous publications [ 14 17 ]. Also, with regard to the vast majority of BCC followed by SCC as underlying tumor entities, the study population shows a typical distribution [ 14 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high functional-esthetical success rate of the modified Hughes procedure, observed in this study, corresponds with the beneficial results, which have been reported in previous publications [ 14 17 ]. Also, with regard to the vast majority of BCC followed by SCC as underlying tumor entities, the study population shows a typical distribution [ 14 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, although Müller’s muscle remained attached to the tarsus, we did not observe a single case of upper lid retraction. The only donor-site complication occurring in this study was a single case of moderate entropium with trichiasis, a finding, which has been described as well in individual cases after complete Müller’s muscle disinsertion from the tarsus [ 14 , 17 ]. In view of this fact, this surgical approach appears suitable not least because a more robust and thicker flap pedicle should reduce the risk of a premature flap dehiscence and consecutively of hypoperfusion and necrosis of the tarsal autograft.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The procedure was proved to be a well-suited technique for eyelid reconstruction of shallow defects extending beyond 10 mm horizontally and involving up to 100% of the eyelid. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Bei unseren Patienten waren Defekte bis 28 mm unter Verwendung der Hughes-Plastik in Kombination mit anderen rekonstruktiven Prozeduren gut wiederherzustellen. Prinzipiell decken sich diese Ergebnisse und die aufgetreten Komplikationen mit denen anderer Autoren [11,12]. Das 1937 von Hughes erstbeschriebene Verfahren [13] eignet sich insbesondere zur Deckung ausgedehnter Unterliddefekte und lässt sich bei kanthaler Mitbeteiligung sowohl isoliert ausführen als auch mit anderen Verfahren kombinieren [11].…”
Section: Materials Und Methodenunclassified